Anatomy of leaves of six Pinus species from the state of Durango, México - de la Paz Pérez Olvera, Carmen; Ceja-Romero, Jacqueline (Instituto de Ecología, A.C., 2019)
México is the country with the highest number of Pinus species in the world, with around 49, of which in Durango there are registered 20. Despite being the genus most used as timber, the information about its leaf characteristics is scarce. Studies about foliar anatomy of Pinus, have shown that some features are useful for their classification, therefore in this paper the morphological and anatomical description of the leaves of six species collected in two municipalities in the state of Durango is presented, in order to determine if there are differences between them that may be useful in this sense. Samples were obtained from herborized material, which was hydrated and processed through the paraffin embedding protocol, to obtain permanent slides. The morphological characters studied were: presence-absence, color and length of the sheath; margin, length and diameter of the needles, number of needles per fascicle. The anatomical characters were: shape of the leaf in cross section, number of stomata rows in superficial view and characteristics of epidermis, mesophyll and vascular system. P. leiophyla was the only species with deciduous sheath. Although in all taxa the shape of the leaf was triangular in cross section, there was variation in the opening of the angles and the position on the resin ducts, however no differences were observed between the representatives of the Ponderosae and Australes subsections, which may have taxonomic utility.